Peace and peace education: A long lasting search for global solution - Spajić-Vrkaš, Vedrana (Array, 2003)
The paper was written in the framework of the EURED project (Education for Europe as Peace Education) carried out by an international group of peace researchers, educators and activists who engaged in discussion on the role of European education in strengthening the post-1989 peace and stability in the world. The author gives an overview of theoretical approaches to peace, as well as of the development of international standards, instruments and actors in this field. Three approaches are described which are relevant for our understanding of the role of the individual, the state and the international community in promoting peace through the respect for freedom, justice and equality, namely peace as a political and legal issue, peace as a spiritual and moral value and peace as a universal human right. The author particularly analyses of differences between armed and positive peace and argues that the former is deeply rooted in a hierarchical notion of peace which necessarily promotes the idea of “ power over others” and “ participation in war” , while the letter emerges from a more egalitarian view and is close to the idea of “ power with others” and “ participation in peace” . In the second part she extends her analysis to the international peace promotion system and reviews the standards, instruments and actors in intergovernmental and non-governmental sectors in relation to recent challenges to peace in Europe.